2017
DOI: 10.1093/jscr/rjx205
|View full text |Cite
|
Sign up to set email alerts
|

A record-breaking lung metastasis from renal cell carcinoma 37 years after nephrectomy

Abstract: Development of distant metastases from renal cell carcinoma (RCC) is a frequent occurrence and, in nearly 95% of the cases, secondary lesions present within 5 years following nephrectomy. We performed a left pneumonectomy for a peri-hilar lung mass in an 81-year-old man with history of kidney cancer, resected 37 years earlier. Histopathological examination revealed a solitary lung metastasis from RCC, relapsed after an extraordinary 37-year time interval. To the best of our knowledge, this remarkable case repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Left pneumonectomy was performed in this patient. The patient was recurrence-free at 3 years follow-up [9]. Genand et al reported solitary lung metastasis in a patient 17 years after nephrectomy for RCC [13].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Left pneumonectomy was performed in this patient. The patient was recurrence-free at 3 years follow-up [9]. Genand et al reported solitary lung metastasis in a patient 17 years after nephrectomy for RCC [13].…”
Section: Discussionmentioning
confidence: 88%
“…Host immune response has been hypothesized to play a role to determine the time for the presentation of RCC metastasis. Duration decreases with compromised immune response [9]. The five and 10-year overall survival rate following pulmonary metastasectomy for metastatic renal cancer was 83% and 41.7% respectively according to Chen et al [14]and 75% and 59% respectively according to Meacciet al [15].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…When breaking down the occurrences of RCC metastatic locations to percentages, the numbers vary considerably, as a result, there are several case reports presenting rare metastatic sites 15 . The mean time for appearance of metastasis of RCC is 1-2 years after operation 16 although in the literature there is a case report with record lung metastasis from RCC 37 years after nephrectomy 17 . When compared to this After surgery the final pathohistological examination confirmed renal cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%